Noninvasive Pediatric Liver Fibrosis Measurement: Two-Dimensional Shear Wave Elastography Compared With Transient Elastography - Tran, Léa Chantal; Ley, Delphine; Bourdon, Gurvan; Coopman, Stéphanie; Lerisson, Héloïse; Tillaux, Céline; Béhal, Hélène; Gottrand, Frédéric; Aumar, Madeleine (Frontiers in Pediatrics, 2022)
Objectives: Although transient elastography (TE) is the primary noninvasive method for assessing liver fibrosis, its use remains to be validated in children. The study aim was to evaluate agreement between two-dimensional ultrasound shear wave elastography (2D-SWE) and TE to assess pediatric liver stiffness method. Methods: During the 18-month study, we prospectively included 101 consecutive children (median age: 8.5 years, range: 1 month–17 years) who required TE for medical reasons, and in whom 2D-SWE measurement was performed within a 3-month follow-up during routine ultrasound. Liver elasticity values were classified according to the Metavir score using published pediatric norms for TE and according to the manufacturer’s reference values for 2D-SWE. Spearman correlation coefficient was used to assess the relation between the elasticity measured by the two techniques. Concordance was described by the Bland–Altman method. Results: A strong correlation (rho=0.70, p<0.001) was found between 2D-SWE and TE for the elasticity measures. The strength of correlation was higher among patients older than 6 years (rho=0.79, p<0.001). Concordance between liver fibrosis stages assessed by these techniques was moderate (weighted kappa=0.46, [95% confidence interval (CI): 0.35–0.57]). When considering stages over F2, 2D-SWE diagnostic performances showed a sensitivity of 85% (95%CI: 74–92) and a specificity of 57% (95%CI: 42–70) compared with TE. Conclusions: Measurements of liver stiffness using 2D-SWE and TE are strongly correlated. The moderate concordance between these techniques for assessing liver fibrosis stage provides evidence against alternating between these methods during follow-up of patients with chronic liver diseases.